2017
DOI: 10.1186/s13018-017-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of L4–S1 Dynesys® dynamic stabilization versus fusion on lumbar motion and its relationship with lumbar degeneration: a retrospective study

Abstract: BackgroundThe aim of this study is to evaluate the efficacy of Dynesys® posterior dynamic stabilization (PDS) in the treatment of L4–S1 degenerative diseases and to assess the influence of postoperative motion on lumbar degeneration.MethodsIncluded in this retrospective study were patients with L4–S1 degenerative disease who underwent fusion or PDS from September 2010 to September 2014. Clinical outcomes were assessed by preoperative and postoperative visual analog scale (VAS) and Oswestry Disability Index (OD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Although the Dynesys system was designed to preserve motion of stabilized segments and prevent degeneration at the adjacent segments by decreasing stress and preventing hypermobility, it is still controversial whether or not dynamic stabilization can prevent the occurrence of ASD. A number of studies have indicated that the Dynesys system can preserve the ROM of the operated segments[ 9 11 28 29 30 ] and prevent radiographic ASD;[ 9 11 31 ] however, some studies showed negative radiographic results with long-term follow-up. [ 10 20 24 ] The severity of diseases included in these studies was relatively severe and the age of the patients was relatively advanced, especially in the St-Pierre study,[ 10 ] in which no patient was excluded based on age; the average age was 76.7 years, 19 patients were in their 80s, and 1 patient was 91 years old at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Dynesys system was designed to preserve motion of stabilized segments and prevent degeneration at the adjacent segments by decreasing stress and preventing hypermobility, it is still controversial whether or not dynamic stabilization can prevent the occurrence of ASD. A number of studies have indicated that the Dynesys system can preserve the ROM of the operated segments[ 9 11 28 29 30 ] and prevent radiographic ASD;[ 9 11 31 ] however, some studies showed negative radiographic results with long-term follow-up. [ 10 20 24 ] The severity of diseases included in these studies was relatively severe and the age of the patients was relatively advanced, especially in the St-Pierre study,[ 10 ] in which no patient was excluded based on age; the average age was 76.7 years, 19 patients were in their 80s, and 1 patient was 91 years old at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the blinding of participants and personnel was of high risk. For the comparative cohort studies assessed by NOS, six studies 3,7,16,19,24,29 were considered to be su ciently high quality, and the seven remaining studies 4,15,17,18,20,22,28 were evaluated as moderate quality.…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…Postoperative ROM Five studies 3,15,19,20,22 provided data on ROM at stabilized segments. The pooled data indicated that the ROM at the stabilized segment in the fusion group decreased signi cantly than that in the Dynesys group (MD = 2.79, 95% CI of 1.84 to 3.75, P< 0.01, I 2 = 97%; Figure 5).…”
Section: Radiographic Outcomesmentioning
confidence: 99%
See 2 more Smart Citations